The origin of bipedality as the result of a developmental by-product: The case study of the olive baboon (Papio anubis). Issue 113 (December 2017) - Druelle, François; Aerts, Peter; Berillon, Gilles
Abstract: In this paper, we point to the importance of considering infancy in the emergence of new locomotor modes during evolution, and particularly when considering bipedal walking. Indeed, because infant primates commonly exhibit a more diverse posturo-locomotor repertoire than adults, the developmental processes of locomotion represent an important source of variation upon which natural selection may act. We have had the opportunity to follow the development of locomotion in captive individuals of a committed quadrupedal primate, the olive baboon ( Papio anubis ). We observed six infants at two different stages of their development. In total, we were able to analyze the temporal parameters of 65 bipedal steps, as well as their behavioral components. Our results show that while the basic temporal aspects of the bipedal walking gait (i.e., duty factor, dimensionless frequency, and hind lag) do not change during development, the baboon is able to significantly improve the coordination pattern between hind limbs. This probably influences the bout duration of spontaneous bipedal walking. During the same developmental stage, the interlimb coordination in quadrupedal walking is improved and the proportion of quadrupedal behaviors increases significantly. Therefore, the quadrupedal pattern of primates does not impede the developmental acquisition of bipedal behaviors. This may suggest that the same basic mechanism is responsible for controlling bipedal and quadrupedal locomotion, i.e., that in non-human primates, the neural networks for quadrupedal locomotion are also employed to perform (occasional) bipedal walking. In this context, a secondary locomotor mode (e.g., bipedalism) experienced during infancy as a by-product of locomotor development may lead to evolutionary novelties when under appropriate selective pressures.